Katuk Leaf (Sauropus androgynus) Puree Incorporation in Milk Sponge Cake: Physical Properties and Consumer Acceptability - Efrina, Thanty; Yeni Yulianti, Mariani (Politeknik Siber Cerdika Internasional, 2024)
Background: The incorporation of plant-based ingredients into bakery products has gained increasing attention as an approach to improve product quality and consumer appeal. Katuk leaf (Sauropus androgynus) is known for its distinctive sensory characteristics, making it a potential ingredient for milk sponge cake formulation. Objective: This study aimed to analyze the effect of katuk leaf puree addition in milk sponge cake on physical properties and consumer acceptability. Methods: This experimental study was conducted at the Food Processing Laboratory, Culinary Education Study Program, Faculty of Engineering, Jakarta State University, from August 2021 to September 22, 2023. The population consisted of Culinary Management students who had completed organoleptic courses. A random sampling technique was applied, involving 30 student panelists. Sensory evaluation covered color, texture, aroma, katuk leaf taste, and sweetness. Data were collected using product assessments and questionnaires and analyzed using the Friedman test and the Tukey test. Results: The results indicated that milk sponge cake with 3% katuk leaf puree was the most preferred formulation, as selected by 80% of expert panelists, while the 6% formulation was selected by 20% of panelists. Overall, the sensory attributes of color, texture, aroma, katuk leaf taste, and sweetness tended to be liked by the panelists. The 3% katuk leaf puree formulation achieved the highest average scores, ranging from 3.8 to 4.6, whereas the 6% formulation obtained lower average scores, ranging from 3.4 to 3.8. Conclusion: The addition of katuk leaf puree significantly influenced the physical properties and consumer acceptability of milk sponge cake. A concentration of 3% katuk leaf puree was identified as the optimal formulation based on overall sensory acceptance.